2014
DOI: 10.2174/1566523214666140424152734
|View full text |Cite
|
Sign up to set email alerts
|

A Suicide Gene Therapy Combining the Improvement of Cyclophosphamide Tumor Cytotoxicity and the Development of an Anti-Tumor Immune Response

Abstract: Gene-directed enzyme prodrug therapy (GDEPT) consists in targeted delivery to tumor cells of a suicide gene responsible for in situ conversion of a prodrug into cytotoxic metabolites. One of the major limitations of this strategy in clinical application was the poor prodrug activation capacity of suicide gene. We built a highly efficient suicide gene capable of bioactivating the prodrug cyclophosphamide (CPA) by fusing a CYP2B6 triple mutant with NADPH cytochrome P450 reductase (CYP2B6TM-RED). Expression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…9,10 In our mouse models, we observed a specific decrease of Tregs upon a weekly administration of CPA. 3 This Treg inhibition might explain, at least in part, the ability of our strategy to induce specific anti-tumor CD8 + T cells.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…9,10 In our mouse models, we observed a specific decrease of Tregs upon a weekly administration of CPA. 3 This Treg inhibition might explain, at least in part, the ability of our strategy to induce specific anti-tumor CD8 + T cells.…”
Section: Introductionmentioning
confidence: 94%
“…Our approach aims at introducing, specifically into tumors, a modified gene which has been constructed and patented in our laboratory (CYP2B6TM-RED = CYP2B6*). [1][2][3][4] This gene transforms very efficiently, inside the tumor, a prodrug (cyclophosphamide, CPA) into toxic metabolites.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, several groups are working to engineer new mutants of CYP2B6 in order to improve the affinity towards CPA. For example, Touati et al (2014), reported the structure of a triple mutant CYP2B6 in fusion with NADPH cytochrome P450 reductase that showed superior ability in converting CPA into its cytotoxic form [130]. While this system has shown great promise at the preclinical level, its safety and efficacy in clinical trials remains to be determined.…”
Section: Enzyme/prodrug Systems: From Bench To Bedmentioning
confidence: 99%